Brain–Blood Partition Coefficient and Cerebral Blood Flow in Canines Using Calibrated Short TR Recovery (CaSTRR) Correction Method - Thalman, Scott W.; Powell, David K.; Ubele, Margo; Norris, Christopher M.; Head, Elizabeth; Lin, Ai-Ling (Frontiers in Neuroscience, 2019)
The brain-blood partition coefficient (BBPC) is necessary for quantifying cerebral blood flow (CBF) when using tracer based techniques like arterial spin labeling (ASL). A recent improvement to traditional MRI measurements of BBPC, called calibrated short TR recovery (CaSTRR), has demonstrated a significant reduction in acquisition time for BBPC maps in mice. In this study CaSTRR is applied to a cohort of healthy canines (n=17, age = 5.0 – 8.0 yrs) using a protocol suited for application in humans at 3T. The imaging protocol included CaSTRR for BBPC maps, pseudo-continuous ASL for CBF maps, and high resolution anatomical images. The standard CaSTRR method of normalizing BBPC to gadolinium-doped deuterium oxide phantoms was also compared to normalization using hematocrit as a proxy value for blood water content. The results show that CaSTRR is able to produce high quality BBPC maps with a 4 minute acquisition time. The BBPC maps demonstrate significantly higher BBPC in gray matter (0.83 ± 0.05 mL/g) than in white matter (0.78 ± 0.04 mL/g, p= 0.006). Maps of CBF acquired with pCASL demonstrate a negative correlation between gray matter perfusion and age (p= 0.003). Voxel-wise correction for BBPC is also shown to improve contrast to noise ratio between gray and white matter in CBF maps. Finally, a strong correlation (R2= 0.81 in gray matter, R2= 0.59 in white matter) is established between BBPC maps normalized to the doped phantoms and BBPC maps normalized using hematocrit. Together this suggests that CaSTRR represents a feasible method to account for BBPC variability when quantifying CBF.